Study of the Drying Kinetics of a Hyaluronic Acid Pellet by Using Terahertz Time-Domain Spectroscopy - Shin, Hee Jun; Park, Jae Hun; Lim, Eun-Kyung; Kim, Hyeung Mun; Huh, Young-Min; Oh, Seung Jae; Ji, Youngbin; Ryu, Han-Cheol (Journal of the Korean Physical Society, 2019)
We measured the moisture content of a hyaluronic acid (HA) pellet by using terahertz time-domain spectroscopy (THz-TDS). The drying dynamics of the HA pellet was investigated using THz-TDS for a 48-h period. During the measurement time, the THz time-domain waveforms of the HA pellet were measured 400 times in a dehydrated chamber, and the refractive index and the absorption coefficient were extracted based on the terahertz signals. The refractive index and the absorption coefficient of the HA pellet were shown to decrease rapidly during the first 4 h and to decrease slowly after 24 h. In addition, the drying kinetics of the HA pellet within the terahertz frequency range was clearly analyzed using a double-exponential fitting model because the measurement of such kinetics demonstrates both fast and slow damping dynamics. The results indicate that the drying kinetics of the HA pellet was successfully analyzed using THz-TDS through a non-contact and non-destructive investigation method and that the THz-TDS can be applied to a study of the drying kinetics of various products, such as foods, cosmetics, and pharmaceuticals.